Image and dosimetry quality control for digital mammography by using the Normi Mam Digital phantom - Calderón-Mata, Angélica (2018)
In Costa Rica there is not an explicit recommendation given by the Regulatory Authorities for the utilization of a specific Phantom; that is why experts have to explore what is offered in the market. One of the most remarkable equipment is Normi Mam Digital made by PTW. This article introduces the results of image and dosimetry quality control, applied to the Normi Mam Digital Phantom to validate how the equipment complies with the recommendations of Human Health Series no. 17. The obtained results were satisfactory and achieved the regulatory tolerances by international sanitary organizations.